All he knew - Frost, Helen, 1949- (Farrar Straus Giroux, 2020)
Henry has been deaf for most of his young life, but when his parents find a school that will teach him, they label him as "unteachable." With little money and no other option, Henry's parents send him to Riverview, an institution for the mentally disabled. There, Henry is subjected to cruel treatment by the staff until he meets Victor, a conscientious objector to World War II, who works as an attendant. Victor can see that Henry is not unteachable and works to get him and other children out of the institution.